Analysis of Prevalance of Dengue Fever in Vavuniya MOH Division - Balachandran, T.; Suthan, S.; Wijekoon, P. (University of Jaffna, 2012)
A descriptive observational study was conducted to identify the demographic, clinical and laboratory profile along with disease outcome of all confirmed cases of dengue fever (DF) and dengue hemorrhagic fever (DHF) admitted in Vavuniya General and Private Hospital. We enrolled 585 patients over a period of three years, beginning from 2007. In 2009, an increase in dengue cases was first noted in the Vavuniya MOH area and there were 7 deaths. During 2009, peoples from the northern part of Vavuniya were displaced to Vavuniya town area due to war. This situation was suitable for mosquito breeding. Most of the parameters between groups showed a similar pattern: mean age of 30 years, mean duration of fever 7 days (range 1-19 days). Mean total white blood cell and platelet counts started to fall from the second day of fever, with the lowest counts between the 5th and 7th days. Majority of the patients affected with DF. It was noted that the majority of the patients are affected within age group of the 20-30 years and 25% of them are children. The sex distribution in this study showed that boys were more sensitive to dengue infection than girls. There is a strong relationship in dengue incidence cases with Gender and age. When considering the variable Village it was seen that the risk factors involved in the areas under study play an important role for transmitting this disease. There is no specific therapy for dengue infections. Good supportive care may be lifesaving, but ultimately initiatives aimed at vector control and prevention of mosquito bites may provide the greatest benefits.
Keywords: DHF; DF; Vavuniya MOH